Brownmillerite‐type Ca2FeCoO5 as a Practicable Oxygen Evolution Reaction Catalyst. Issue 14 (19th June 2017) - Tsuji, Etsushi; Motohashi, Teruki; Noda, Hiroyuki; Kowalski, Damian; Aoki, Yoshitaka; Tanida, Hajime; Niikura, Junji; Koyama, Yukinori; Mori, Masahiro; Arai, Hajime; Ioroi, Tsutomu; Fujiwara, Naoko; et al.
Abstract: Here, we report remarkable oxygen evolution reaction (OER) catalytic activity of brownmillerite (BM)‐type Ca2 FeCoO5 . The OER activity of this oxide is comparable to or beyond those of the state‐of‐the‐art perovskite (PV)‐catalyst Ba0.5 Sr0.5 Co0.8 Fe0.2 O3− δ (BSCF) and a precious‐metal catalyst RuO2, emphasizing the importance of the characteristic BM structure with multiple coordination environments of transition metal (TM) species. Also, Ca2 FeCoO5 is clearly advantageous in terms of expense/laboriousness of the material synthesis. These facts make this oxide a promising OER catalyst used in many energy conversion technologies such as metal–air secondary batteries and hydrogen production from electrochemical/photocatalytic water splitting. Abstract : A winning combo : We report remarkable oxygen evolution reaction (OER) catalytic activity of brownmillerite (BM)‐type Ca2 FeCoO5 in alkaline media. The combination of tetrahedral and octahedral sites in the BM structure plays a crucial role in the observed OER activity, which is comparable to or beyond those of the state‐of‐the‐art perovskite catalysts and a precious‐metal catalyst RuO2 .